Pengembangan Media Audio Menyimak Tematik Berbasis Fitrah Bagi Siswa Sekolah Dasar - Muhamad Fakhrur Saifudin; Hanum Hanifa Sukma (Jurnal Inovasi Pendidikan Dasar, 2020)
This study aims to (1) Develop audio media with thematic listening skills based on the nature of elementary school students; (2) find out the feasibility of thematic listening media audio media based on the nature of elementary school students. The method used in this research is the research and development method. The model used is the ADDIE model consisting of 5 (five) steps, namely: (1) analysis (analyze), (2) design, (3) development, (4) implementation, and ( 5) evaluation. The results showed that based on the feasibility test based on the material, learning, and language expert validators stated that the media listened to thematic audio based on fitrah with the "very appropriate" criteria. The results of the field trials show the feasibility of the media as a thematic learning tool for elementary school at 86.5% so that it can be used as an alternative in the choice of listening learning media.